Eutanasia en casos no terminales: ética de la autonomía del paciente y sufrimiento insoportable sin tratamiento viable - Ordoñez Ruiz, Lissette Melissa (2025)
The research analyses the possibility of using euthanasia in non-terminal cases in Ecuador, focusing on the ethics of patient autonomy and unbearable suffering without viable treatment. The recent approval of euthanasia by the Constitutional Court in 2024 poses challenges in medical practice and the need for a clear deontological framework. At an international level, countries such as the Netherlands, Belgium and Colombia have allowed euthanasia in cases of incurable diseases, even without being terminal. The study examines the ethical and legal justification of this practice in Ecuador, where the regulations are still incipient and present gaps in the definition of "unbearable suffering". Regulations from countries with a longer history of euthanasia are compared to identify lessons applicable to the Ecuadorian context. Ethical dilemmas are analyzed, such as medical conscientious objection and the risk of a "slippery slope", where euthanasia could be expanded to cases not initially contemplated. International emblematic cases are also studied to evaluate the practical challenges in the implementation of this practice. The study concludes that, although patient autonomy may justify euthanasia in non-terminal cases, its application in Ecuador requires a detailed regulatory framework that guarantees the protection of patient rights and medical ethics, avoiding abuses and ensuring the quality of health care.